3D Printed Patient Specific Surgical Guide for Spine Registration During Minimally Invasive Surgery - Hujaleh, Iffa (Université d'Ottawa / University of Ottawa, 2021)
Minimally invasive spine surgery (MISS) has proven to be advantageous over traditional open surgery as it minimizes the likelihood of tissue damage and infections. During MISS, surgeons create small incisions to allow access to the surgery site, however, opting for smaller incisions decreases the surgeon’s field of vision. To compensate, surgeons rely on preoperative and intraoperative ionizing imaging technologies for guidance. Conventional localization of the spine, registration of digital images to the patient during surgery, depends heavily on the surgeon’s anatomical knowledge and their experience. Preoperative images are typically created using 3D technology while intraoperative images use 2D technology. While the integration of preoperative 3D images and intraoperative 2D images can provide valuable assistance, patient’s preoperative and intraoperative positions do not coincide leading to additional use of ionizing imaging. The objective of this research was to propose a workflow that assists with image registration for MISS. The main component of the workflow was the creation of a script that automatically generates patient-specific digital guides, which will then be manufactured, to align the patient’s intraoperative and preoperative body position. By aligning the patient’s positions, the 3D printed surgical guide serves as a shared feature between the preoperative digital image and the actual patient. This allows for the intraoperative image to be registered to the preoperative image more accurately. Additionally, the guide acts as an attachment site for any additional instrument guides/supports. The surgical guide generating script utilizes the skin contour of patient’s torso region, extracted from medical images, to automatically produce the guide’s horizontal and vertical components. Adjustments are made to the components using CAD software before proceeding to manufacturing, via 3D printing, and assembly of the guide. To validate the workflow, more specifically the script’s ability to automatically generate surgical guides that fit over the patient’s back, a guide was created for a mannequin. The maximum gap between the mannequin and the horizontal components was 0.8 cm and 1.5 cm for the vertical component.
Keywords: 3D printing; Surgical guide; Minimally invasive surgery; Spine surgery; Image registration; Patient specific